ANALISIS FAKTOR YANG MEMPENGARUHI PENGELUARAN PER KAPITA PROVINSI DAERAH ISTIMEWA YOGYAKARTA DENGAN PENDEKATAN REGRESI LINIER SEDERHANA - Nurul Latifah; Moh Yamin Darsyah (Universitas Muhammadiyah Semarang, 2017)
The advanced society will absolutely prefer to expend much money for education, healthy, and entertainment than for their needs of food. This analysis is expected to know the level of safety and strategy to decrease the society's level of consumption. The analysis result by simple regression approach sho, w : The expending in each capita variable (Y) and level of economic increasement (X1). By another words, the expending factor in each capita is affected by the level of economic increasement in the amount of 72.71%. Meanwhile, the rest is in the amount of 27.29% affected by another factor. The expending of each capita is affected by the level of economic increasement. By this, the amount of R-Square score is 0.7271. If R-Square increases higher, it can be said that the set of problems are better.Keywords: simple regression approach, the expending in each capita, Yogyakarta